Midwifery Students’ Attitude in Learning English Conversations in The Classroom Setting - Sarma Dewi Kemala; Herawati Bukit (JETLi: Journal of English Teaching and Linguistics, 2022)
In the global era, English is a mandatory material that must be used as teaching material for midwifery students. This is important; because it cannot be denied that midwives in Indonesia often encounter obstacles when serving foreigners. It is quite difficult for them to have a dialogue with tourists, even though at this time our country is increasingly being visited by foreigners, whether for holidays, research, or student exchange. It is not impossible, to engage or converse with them while they are experiencing health problems, or just need a check-up. This study is aimed at describing the types of midwifery students’ attitude toward English conversation, elaborate realization of Midwifery students’ attitude toward English conversation, and reasons for the midwifery student’s reality their attitudes toward English conversation. Qualitative study is conducted. The subjects of this study were 55 students. The data were collected by interviews. Some results, firstly they were positive and negative attitudes toward English conversation class, nine realizations, and four reasons of the students realized i.e. (1) language pride, (2) awareness of language norms, (3) motivation to get the job, and (4) lack of skill. It was concluded the students attitude varied as to positive and negative ones and real numerous manners affected by several factors.